Spinal anaesthesia in kyphoscoliotic parturients undergoing caesarean delivery - A retrospective study from a tertiary care centre in India - Ranju Singh; Rashi Sardana; Pooja Singh (Wolters Kluwer Medknow Publications, 2022)
Introduction: Kyphoscoliosis with pregnancy is a rare but serious disorder which often requires caesarean delivery. Both general and regional anaesthesia have been used in these cases but data regarding outcomes with spinal anaesthesia (SA) are limited. Methods: We conducted a retrospective study to identify patients with kyphoscoliosis undergoing caesarean delivery at a tertiary care hospital in India. Those parturients who received SA were compared with those receiving general anaesthesia (GA group) with respect to cardiorespiratory parameters, maternal outcomes and neonatal outcomes. Results: The GA group had significantly worse cardiorespiratory parameters including pulmonary function tests, right atrial pressures and cardiac ejection fraction as compared to SA group. All the GA group patients required mechanical ventilation while no patients in the SA group needed mechanical ventilation. Intraoperative hypotension was more common in the SA group. Neonatal outcomes were worse in the GA group with lower Apgar scores at 1 and 5 min and more nursery admissions than the SA group. No maternal or neonatal deaths occurred in either group. Conclusion: Kyphoscoliotic parturients scheduled for CD can be successfully managed with SA with good maternal and neonatal outcomes. GA may be reserved for severe kyphoscoliotic parturients with cardiorespiratory complications. The safety of SA in severe kyphoscoliosis requires further studies.